Entry and exit points: violent extremism in South-East Asia - Schonveld, Ben; Templer, Robert; Giacoma, Jim-Della; El-Muhammady, Ahmad (UNDP, 2020)
Violent extremism remains a significant challenge for South-East Asia, but in no country does it pose an existential threat. In Indonesia, Malaysia, Myanmar, the Philippines and Thailand, governments have the capacity to prevent it, while at the same time they should understand that it is unlikely to disappear completely. Whether violent extremism spreads, or is minimized, depends largely on how states react to its presence.